2018
DOI: 10.1128/mbio.00036-18
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Susceptibility of Meningococcal Serogroup B Isolates to Bactericidal Antibodies Elicited by Bivalent rLP2086, a Novel Prophylactic Vaccine

Abstract: Bivalent rLP2086 (Trumenba), a vaccine for prevention of Neisseria meningitidis serogroup B (NmB) disease, was licensed for use in adolescents and young adults after it was demonstrated that it elicits antibodies that initiate complement-mediated killing of invasive NmB isolates in a serum bactericidal assay with human complement (hSBA). The vaccine consists of two factor H binding proteins (fHBPs) representing divergent subfamilies to ensure broad coverage. Although it is the surrogate of efficacy, an hSBA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 45 publications
(63 reference statements)
1
53
0
Order By: Relevance
“…With the advancement of new antibody-discovery technologies (immune receptor identification), we believe that this promises to be a rapidly growing field in the near future. Generation of complement-activating antibodies is also considered important for the protective action of multivalent Neisseria vaccines that trigger the formation of antibodies that kill bacteria via MAC or phagocytosis [64,65]. A potent vaccine candidate in N. meningitidis is factor H-binding protein (fHBP), an outer membraneassociated lipoprotein that recruits factor H and thereby downregulates complement activation.…”
Section: Exploiting the Action Of Complement In Immune Therapies Agaimentioning
confidence: 99%
“…With the advancement of new antibody-discovery technologies (immune receptor identification), we believe that this promises to be a rapidly growing field in the near future. Generation of complement-activating antibodies is also considered important for the protective action of multivalent Neisseria vaccines that trigger the formation of antibodies that kill bacteria via MAC or phagocytosis [64,65]. A potent vaccine candidate in N. meningitidis is factor H-binding protein (fHBP), an outer membraneassociated lipoprotein that recruits factor H and thereby downregulates complement activation.…”
Section: Exploiting the Action Of Complement In Immune Therapies Agaimentioning
confidence: 99%
“…MenB‐FHbp contains two FHbp variants, one each from subfamilies A and B, and is sufficient to provide broad coverage against the diversity of disease‐causing MenB strains; >99% of 650 US strains surveyed by the CDC contain FHbp , and >91% of invasive MenB strains express FHbp at sufficient levels to be susceptible to bactericidal antibodies elicited by the vaccine . MenB‐4C is composed of four protein antigens present in variable percentages of 442 US strains surveyed by the CDC: recombinant FHbp subfamily B fusion protein (53% of strains); recombinant neisserial heparin‐binding antigen fusion protein (NHBA; 83% of strains); recombinant neisserial adhesin A protein (NadA; 2.5% of strains); and outer membrane vesicles containing PorA (5.9% of strains) .…”
Section: Resultsmentioning
confidence: 99%
“…The level of fHbp expression has been found to be a key determinant of bactericidal susceptibility to anti-fHbp antibodies (Jiang et al, 2010). Pre-clinical studies have indicated that as many as 19% of strains expressing fHbp variant 2 or 3 may not be susceptible to bactericidal killing by MenB-fHbp-induced antibodies because they express insufficient antigen on the cell surface (McNeil et al, 2018). Similarly, protection would not be expected against strains that do not express fHbp.…”
Section: Role and Contribution Of Fhbpmentioning
confidence: 99%